Determinants of orality in dedications of medical handbooks from the second half of the 18th century - Pasternak, Simone (Papers in Linguistics, 2025)
The aim of the article is to identify the determinants of secondary orality and traces of spoken language in dedication letters included in three 18th-century medical handbooks. Originally, dedications belonged to the spoken variety of language, and in the second half of the 18th century as a genre they structurally resembled speeches. To describe the determinants, the study addresses punctuation marks, which were previously used according to the intonational-declamatory principle. Early Polish grammars recommended using punctuation in a way to indicate changes in intonation or the length of pauses between text segments. The authors of the studied works employed punctuation marks to signal a potential interpretation of the text, but also introduced rhetorical devices often used in oratory. It also appears that the temporal difference in voice suspension, determined by colons and semicolons, was problematic, hence these marks were used in the same functions or one of them was omitted. In the 18th-century dedication genre, signals of orality and spoken language can be found, expressed through the used rhetorical means or in the expressive function of the works. Conclusions from the current study also provide a basis for further research on punctuation in historical texts.